Anaya Honey: a story of sweet success - Makuzwa, Kuda (Henry Stewart Talks, 2019)
Entrepreneur, Entrepreneurship, Start-up, Zimbabwe, Honey, Bee-keeping, Emerging economies, Intuitive Intelligence, Decision making